Therapeutic Study of Thermosensitive Hydrogel Loaded with Super-Activated Platelet Lysate Combined with Core Decompression Technology for the Treatment of Femoral Head Necrosis - Zhipeng Huang; Zhe Zhao; Jun Lang; Wantao Wang; Yinsheng Fu; Wenbo Wang (Hindawi Limited, 2021)
Super activated platelet lysate (sPL) is a derivative of platelet-rich plasma (PRP) that contains high levels of several growth factors. In this study, we synthesized a temperature-sensitive hydrogel that contained temperature-sensitive Poly(DL-lactide-glycolide-glycolide acid) (PLGA), SrCl2, and HA, and loaded it with different concentrations of sPL. The hydrogel showed satisfactory encapsulation efficiency and release of the growth factors in a sustained manner, indicating its suitability as a drug carrier. The sPL-loaded hydrogel was inserted into the necrotic femoral head of a rat model and core decompression was applied and resulted in significantly accelerated bone repair and regeneration. Therefore, encapsulation of sPL in a hydrogel scaffolding may be an effective strategy for treating femoral head necrosis.